Correlation between Von Spee’s Curve and Vertical Dental Eruptions in Class II Division-2 Malocclusion - Azeem, Muhammad; Hamid, Waheed Ul; Haq, Arfan Ul; Ijaz, Huma (Orthodontic Journal of Nepal, 2017)
Introduction: Von Spee’s curve is one of the important treatment aspects in orthodontics. Any orthodontic treatment planning is dependent on this key factor. Objective: To find out the correlation between the Von Spee’s curve and occlusal eruption of anterio-posterior teeth in Class II Division 2 malocclusion. Materials & Method: Current research was conceived at the Department of Orthodontics, de’Montmorency College of Dentistry and Faisalabad Medical University. Two hundred and fifty Class II Division 2 patients (112 male, mean age: 15.1±1.5 years; 138 female, mean age: 15.4± 1.3 years) were included. Depth of the curve was calculated on lateral cephalograms and dental plaster models, and correlated with the vertical eruption of lower incisal teeth and posterior mandibular molars. Result: The mesiobuccal site of mandibular first molar was the deepest part of Von Spee’s curve, and vertical eruption of lower incisal teeth were more related to depth of Von Spee’s curve as compared to vertical eruption of mandibular molars. Conclusion: Vertical eruption of the mandibular molar teeth make significant contribution to the depth of Von Spee’s curve in Class II Division 2 malocclusion.